The Effect of Entrepreneurial Orientation, Product Innovation, and Digitalization on Business Performance (Survey of Seblak MSMEs Actors in Sukabumi City) - Taopik, Moh.; Jhoansyah, Dicky; Saori, Sopyan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to analyze the influence of entrepreneurial orientation, product innovation, and digitalization on business performance among MSMEs seblak entrepreneurs in Sukabumi City. Based on the results and discussion, several main conclusions were drawn. Entrepreneurial orientation is reflected through risk-taking, where MSMEs entrepreneurs dare to try new business strategies and face market uncertainties to achieve business growth. Product innovation is an important aspect, with the addition of seblak variants continuously developed to meet diverse consumer needs. Digitalization is increasingly adopted, particularly in digital ordering through social media platforms and e-commerce, which facilitates consumers in ordering products online, expands market reach, and improves operational efficiency. The results show that entrepreneurial orientation has a positive and significant effect on business performance among MSMEs seblak entrepreneurs in Sukabumi City, as evidenced by the t-value being greater than the t-table value. Additionally, product innovation also has a positive and significant impact on business performance, indicated by the t-value being greater than the t-table value. Lastly, digitalization is proven to have a positive and significant effect on business performance, as evidenced by the t-value being greater than the t-table value. These findings underline the importance of entrepreneurial orientation, product innovation, and digitalization in improving the business performance of MSMEs seblak in Sukabumi City.